PERBEDAAN KADAR ASAM URAT PADA ORANG YANG GEMAR MENGKONSUMSI KOPI DAN MEROKOK DENGAN ORANG YANG HANYA GEMAR MENGKONSUMSI KOPI - Fahmi, Norma Farizah; Putri, Devi Anggraini; Putri, Nivia (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2020)
Uric acid is a crystal formed from the metabolism of purines. In men, gout is dangerous if more than 7 mg / dl, whereas in women 6 mg / dl. In Indonesia 35% of gout occurs in men under the age of 35 years. The purpose of this study was to analyze the differences in uric acid levels in people who like to consume coffee and smoke with people who only like to consume coffee in Mlajah Bangkalan Village. The research design used is comparative analytic. The variables in this study were uric acid levels and people consuming coffee and smoking with people consuming coffee only. The population in this study was 2,775 households in Mlajah Bangkalan Urban Village. Respondents in this study were 9 people consuming coffee and smoking, and 9 people were consuming coffee. The instrument used was POCT (Point Of Care Testing) using capillary blood. Data were analyzed using Independent Sample t Test. The results of this study indicate normal uric acid levels of people drinking coffee and smoking with an average value = 5 and the average value of uric acid levels in people only drink coffee = 4.67. The p-value = 0.587 (> from the alpha value of 0.05) so that there is no difference in the levels of uric acid levels in people who like to consume coffee and smoke with people who only like to consume coffee.